Agility-based exercise training compared to traditional strength and balance training in older adults: a pilot randomized trial - Eric Lichtenstein; Mareike Morat; Ralf Roth; Lars Donath; Oliver Faude (PeerJ, 2020)
Background In addition to generally high levels of physical activity, multi-component exercise training is recommended for the maintenance of health and fitness in older adults, including the prevention of falls and frailty. This training often encompasses serial sequencing of balance, strength, endurance and other types of exercise. Exercise training featuring integrative training of these components (i.e. agility training) has been proposed, as it more likely reflects real life challenges like stop-and-go patterns, cutting manoeuvers, turns and decision-making. In this study, we compared the efficacy of an agility-based training to the traditional strength and balance training approach with regard to selected risk factors for falls and frailty. Methods We trained twenty-seven community-dwelling healthy seniors (16♂; 11♀; age: 69.5 ± 5.3 y; BMI: 26.4 ± 3.7 kg/m2) for 8 weeks in a group setting with 3 sessions per week, each lasting 50 minutes. Participants were randomized into either the agility group (AGI; n = 12), that used the integrative multi-component training, or the traditional strength and balance group (TSB; n = 15). TSB performed balance and strength exercises separately, albeit within the same session. The training of both groups progressively increased in difficulty. Outcomes were static and dynamic balance (single leg eyes open stand, Y-balance test, reactive balance), lower limb (plantar flexion and dorsal extension) and trunk flexion and extension maximum strength and rate of torque development (RTD). In addition, we tested endurance by the six-minute walk test (6MWT). We calculated linear mixed effects models for between-groups comparisons as well as effect sizes (ES) with 95 % confidence intervals. Results Small ES in favor of AGI were found for plantar flexion strength (ES > 0.18[−0.27;0.89]) and RTD (ES > 0.43[−0.19;1.36]) as well as trunk extension RTD (ES = 0.35[−0.05;0.75]). No other parameters showed notable between group differences. Compliance was high in both groups (AGI: 90 ± 8% of sessions; TSB: 91 ± 7% of sessions). Discussion Agility-based exercise training seems at least as efficacious as traditional strength and balance training in affecting selected physical performance indicators among community-dwelling healthy seniors. In particular, lower limb and trunk extension explosive strength seem to benefit from the agility training.